Karakteristik Kimia Tanah Dari Lahan Agroforestri Kawasan Hutan Pendidikan Universitas Mataram Di Desa Senaru, Kabupaten Lombok Utara - Vilia Rosalina; Lalu Arifin Aria Bakti; Sukartono Sukartono (Department of Soil Science, Faculty of Agriculture, University of Mataram, 2023)
This study aims to evaluate the chemical characteristics of the soil from agroforestry land on various types of land cover in the Unram Educational Forest, Senaru Village, Bayan District, North Lombok Regency. This research was carried out in the Senaru Educational Forest, North Lombok and soil analysis was carried out at the Soil Chemistry and Biology Laboratory, Faculty of Agriculture, University of Mataram in September-November 2022. The method used in this study was a descriptive method using a field survey technique. The descriptive method begins with data collection, data analysis and data interpretation. Soil chemical characteristics (pH, C-organic, Cation Exchange Capacity (CEC), Nitrogen, Phosphorus, and Potassium) were obtained by analysis in the laboratory. The results of this study indicate that the chemical characteristics of the soil in the Senaru Educational Forest Area with Special Purposes (KHDTK) are relatively the same. In general, soil fertility status, especially nutrient status (pH, C-organic, Cation Exchange Capacity (CEC), Nitrogen, Phosphorus, and Potassium) ranges from good to very good.